The book of basketball : the NBA according to the sports guy - Simmons, Bill. (New York : Ballantine/ESPN Books, 2009)
Bill Simmons, the from-the-womb hoops addict known to millions as ESPN.com's Sports Guy, offers in a single volume his wildly opinionated and thoroughly entertaining look at the past, present, and future of pro basketball.
Includes bibliographical references (p. [701]-702) index.
Keywords: National Basketball Association; Basketball